FAKTOR DOMINAN PENENTUAN PEMENANG LELANG PADA SISTEM GUGUR DI KOTA BANDA ACEH - Alfa Taras Bulba; Muammar Zaki Fahlewi (JURNAL TEKNIK SIPIL, 2014)
Tender stage is a process to be appointed  contractor for construction project implementation. Bidding method is used by sistem gugur that divided into administration, technic and prices evaluation. The purposed of research is to identify dominan factors that influence to contractor selection between 2010 until 2013 at Banda Aceh. Data is collected from contractor who is in charges likes Project Manager, Engineer and ULP as a parties from owner to selecting contractor. Dominan factor variabel is measure by Linkert scale and Guttman scale also to measured relationship each factors in deciced variable. Data is showedcontractor fail the bid because administration evaluation 13,25%, technich evaluation 8,55%, price evaluation 7,69% and cancel of bid 70,79%. Reability test result is cornbach alpha0,80320,6. Dominan factor is rated from organisation factor such as communication, documentation and coordination 95,83%, human resources 81,11%, financial factor 80,37%,machinery and tools 74,81% and experiences factor 56,67%. This research result can be input to the parties are involved to be tender stage implementation.